Nursing students perspectives of psychosocial care: cross-sectional study - Ahmad H. Al-Nawafleh; Falah Zaal Altarawneh (BMC Nursing, 2023)
Abstract Background Psychosocial care is an integral component of holistic nursing practices. This study aimed to examine how fourth-year nursing students at Mutah University perceive various care characteristics, specifically psychosocial care. Methods A quantitative cross-sectional study was conducted using the Caring Dimension Inventory (CDI). Data were obtained from 105 nursing students before graduating from a Jordanian public educational institution. Data analyzed using the scoring of CDI and descriptive statistics. Results The mean scores in the professional and technical domain of care were statistically higher for fourth-year nursing students (4.69 ± 0.25). This exceeded their scores in the psychosocial domain of care (3.37 ± 1.20). This suggests that fourth-year nursing students prioritize professional and technical care over psychosocial care. Conclusions Fourth-year nursing students tended to perceive the technical aspects of care as more significant than the psychosocial aspects. This highlights the need for nursing schools and healthcare providers to reconsider their focus and prioritize the importance of psychosocial care.